The Influence of Work-Life Balance and Career Development on Job Satisfaction of Employees of PT Charoen Pokphand Indonesia Sepanjang Plant - Sinulingga, Rosalina Theresia; Swasti, Ika Korika (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The purpose of this study was to determine and examine the effect of career development and work-life balance on the job satisfaction of employees of PT Charoen Pokphand Indonesia Sepanjang Plant. The entire population is used as a research sample in this quantitative research design, which also uses probability sampling techniques with a total of 50 respondents by census. To ensure the accuracy and consistency of the data, questionnaires that had undergone validity and reliability tests were distributed to collect the data. SmartPLS4 software was used to analyze the data. By using the partial least squares (PLS) analysis approach combined with the structural equation model (SEM) to test the hypothesis of this study. The Likert scale was used as the measurement scale in this study. The findings of this study explain that employee job satisfaction is positively and significantly influenced by work-life balance. Employee job happiness is positively and significantly influenced by career growth.